2013
DOI: 10.1021/ja400227q
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Mechanisms for the Formation of Substituted Azanaphthalenes through Consecutive CN and C2H Additions to Styrene and N-Methylenebenzenamine: A Theoretical Study

Abstract: Ab initio G3(MP2,CC)/B3LYP/6-311G** calculations of potential energy surfaces (PESs) for the reactions of cyano and ethynyl radicals with styrene and N-methylenebenzenamine have been performed to investigate a possible formation mechanism of the prototype nitrogen-containing polycyclic aromatic compounds: (substituted) 1- and 2-azanaphthalenes. The computed PESs and molecular parameters have been used for RRKM and RRKM-Master Equation calculations of reaction rate constants and product branching ratios under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Recent studies exploiting a pyrolytic reactor revealed indeed that the reaction of pyridyl radicals with acetylene does lead to the formation of (iso)­quinoline, the nitrogen-substituted counterparts of naphthalene involving HACA-type reaction pathways . Theoretically, we demonstrated that NPAH can be also formed at low temperatures through consecutive CN and C 2 H additions to styrene and N -methylenebenzenamine . Therefore, these findings provide new insights into the formation mechanisms of aromatic molecules incorporating nitrogen atoms through gas phase radical mediated reactions in high-temperature circumstellar envelopes, and hopefully in future studies through vinylacetylene- or C 2 H/CN-mediated reactions in low-temperature interstellar environments such as in cold molecular clouds.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Recent studies exploiting a pyrolytic reactor revealed indeed that the reaction of pyridyl radicals with acetylene does lead to the formation of (iso)­quinoline, the nitrogen-substituted counterparts of naphthalene involving HACA-type reaction pathways . Theoretically, we demonstrated that NPAH can be also formed at low temperatures through consecutive CN and C 2 H additions to styrene and N -methylenebenzenamine . Therefore, these findings provide new insights into the formation mechanisms of aromatic molecules incorporating nitrogen atoms through gas phase radical mediated reactions in high-temperature circumstellar envelopes, and hopefully in future studies through vinylacetylene- or C 2 H/CN-mediated reactions in low-temperature interstellar environments such as in cold molecular clouds.…”
Section: Discussionmentioning
confidence: 50%
“…109 Theoretically, we demonstrated that NPAH can be also formed at low temperatures through consecutive CN and C 2 H additions to styrene and N-methylenebenzenamine. 110 Therefore, these findings provide new insights into the formation mechanisms of aromatic molecules incorporating nitrogen atoms through gas phase radical mediated reactions in high-temperature circumstellar envelopes, and hopefully in future studies through vinylacetylene-or C 2 H/CN-mediated reactions in low-temperature interstellar environments such as in cold molecular clouds. The experimental and theoretical results discussed in the present work demonstrate very significant pressure dependence for the rate constants, especially the product-channel specific rate constants.…”
Section: Discussionmentioning
confidence: 84%
“…This can be achieved by formally replacing the phenyl radical reactant (C 6 H 5 ) by a pyridyl radical (C 5 H 4 N) formed via hydrogen abstraction from pyridine (C 5 H 4 N). The latter is predicted to be synthesized at high temperatures via the reaction of HCN with two acetylene molecules, which are abundant in circumstellar envelopes of carbon stars (Cherchneff 2011;Landera & Mebel 2013). However, as of now, the formation mechanisms of even the prototypical representatives of NPAHs-quinoline and its isomer isoquinoline as detected in the Murchison meteorite (Plows et al 2003)-remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, free radical mechanisms using CN radicals toward the formation of azanaphthalenes have been proposed as a viable route on Titan. 10,11 Many studies indicated formamide to be active in photolytic reactions. For example, formamide adds to olefins under photolytic conditions in the presence of acetone.…”
Section: Introductionmentioning
confidence: 99%